O-12 Getting the word out there – one hospice's internal communications journey with an intranet. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Gray, Sarah
Abstract : Background: With 24 shops, over 400 volunteers and 150 shift workers with little access to a computer, internal communication was a perennial challenge cited in staff surveys. Combined with a burgeoning shared drive and multifarious emails pinging around inboxes, we looked for a user-friendly solution that would balance a Facebook style community with well governed data sharing. Aims: Engage hard-to-reach staff and volunteers working off site, on shifts and on the bank Create dynamic content relevant to the audience Empower users to blog, write content and comment Move relevant data off a shared drive within an information governance framework. Methods: As runners up in an Interact Intranet competition in 2015, we received a year's free intranet for all staff and volunteers; cloud based for remote access. A pan-hospice working group decided on structure and content as the model had to be built from scratch. Launch date coincided with our Christmas party, allowing staff to upload and view photos thereby providing the perfect logon hook. Results: Six months in and overall staff feedback has been positive: A recent intranet survey revealed that 90% of respondents found it easy to find information Governance groups now upload minutes and papers onto the intranet Teams are slowly building their own spaces to share news and views Images tell a thousand words: our intranet captures this perfectly. Interpretation and conclusions: Our intranet is now the go-to place for internal communications. Engagement takes time and persistence though. Investing in training to build up confidence in usage is paramount, as is keeping content fresh and relevant. Our volunteers are reluctant users so we will revisit this as a worthwhile channel of communication with them when we look to paying for our second year. However, as we look towards the end of our first intranet year it looks like there is no going back to the old-fashioned staff newsletter.